2020
DOI: 10.1155/2020/5965328
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Graphite Tailings and Curing Conditions on the Early‐Age Performances of Cement Mortar

Abstract: In this study, the combined effects of different amounts of graphite tailings (GT) as a substitute for sand and three cure methods on the early-age mechanical and material performances of cement mortar have been investigated. The results can be concluded that graphite tailings and hot-water cure method can effectively improve the early strength of cement-based materials and facilitate the formation of high-density calcium silicate hydrate (C-S-H), more Ca(OH)2 (CH), and other hydration products. Simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…The environmental loads related to nuclear energy for the analyzed batteries are of a similar type. For each battery, they include the exploitation of an underground uranium mine [89], and for lithium-ion and lithium iron phosphate batteries they also involve the exploitation of an open-pit uranium mine, as also confirmed in [90]. In turn, lithium iron phosphate batteries are also characterized by loads from uranium production in cake and leaching on site.…”
Section: Environmental Loads Analysis For Nuclear Energymentioning
confidence: 91%
See 1 more Smart Citation
“…The environmental loads related to nuclear energy for the analyzed batteries are of a similar type. For each battery, they include the exploitation of an underground uranium mine [89], and for lithium-ion and lithium iron phosphate batteries they also involve the exploitation of an open-pit uranium mine, as also confirmed in [90]. In turn, lithium iron phosphate batteries are also characterized by loads from uranium production in cake and leaching on site.…”
Section: Environmental Loads Analysis For Nuclear Energymentioning
confidence: 91%
“…Possible ways of improving the quality of quicklime, including reducing its negative environmental impact [73] Resource depletion assessment for NCM batteries [33] Heat production, hard coal Proposition of a procedure for preoxidation in the gas/liquid phase as part of the inoculation of oxygen cross-links in bituminous coal [74] Research involving uncontrolled exothermic reactions as part of the safe design of a battery system with testing on various heating systems [89] Road construction…”
Section: Electricity Production Hard Coalmentioning
confidence: 99%
“…There has been rare research on GT environment-friendly concrete. Liu et al [37][38][39][40][41][42] prepared GT concrete with high electrical conductivity, frost resistance, and mechanical properties. Kathirvel, P. et al [43] suggested that the optimal mechanical properties and durability can be obtained when GT are replaced by 40% volume content of sand.…”
Section: Comparison Of Gt and Sand Mesoscopic Picturesmentioning
confidence: 99%
“…It can be found that the incorporation of 20% graphite tailings mainly causes the contraction vibration of -OH (3640) functional group in Ca(OH) 2 without the incorporation of basalt fibres. With the addition of basalt fibres, the absorption peaks of -OH (3640) functional group vibrations changes from strong to weak, indicating that graphite tailings and basalt fibres inhibit the formation of Ca(OH) 2 in cement mortar [49]. This may be caused by the hydrophilic nature of graphite tailings and basalt fibres, resulting in insufficient bound water in the mortar during hydration; it may also be reflected laterally by the change in the bending vibration of H-O-H (1640) to lower the absorption peak of the -OH (3640) functional group.…”
Section: Analysis Of Functional Group Changes In Bfr-gtcmmentioning
confidence: 99%